Criminological Review Of The Phenomenon Of Verbal Sexual Harassment Against Women In Indonesia - Vevti Al Putriana. A; Herlita Eryke (UNIVERSITAS PAKUAN, 2026)
Verbal sexual harassment against women is a common phenomenon in Indonesia and is often considered trivial by some, despite its significant impact on women's psychological well-being, sense of security, and freedom to engage in activities in both public and private spaces. This study aims to examine the phenomenon of verbal sexual harassment against women in Indonesia from a criminological perspective, emphasizing the causal factors, perpetrators' behavioral patterns, and the impacts experienced by victims. This research uses a normative legal research type with a criminological approach through a literature study method of various legal sources, books, and relevant scientific journals. The results of the study indicate that the occurrence of verbal sexual harassment is influenced by patriarchal social construction, low public awareness and understanding of forms of sexual harassment, weak law enforcement, and the existence of social stigma against victims, which causes many victims to be reluctant to report their experiences. Therefore, needed through increasing public education, strengthening the legal framework, and providing adequate support for victims to create a safer and more equitable environment for women in Indonesia. Keywords: Criminology, Verbal Sexual Harassment, Women, Gender-Based Violence, Social Norms, Victimology, Sexual Harassment, Social Control Theory